Measuring Stress Level Among Medical Students - Timotius Girsang, Ronaldo; Napiah Nasution, Ali; Manalu, Putranto; Wahyuni Nasution, Sri (International Journal of Health and Pharmaceutical (IJHP), 2022)
Measurement of stress levels is important considering the long and stressful study period that medical students have to go through. This study aims to measure the difference in stress levels of the first year and third-year medical education students. The approach used in this study is a one-time unpaired numerical comparative analysis of two groups with a cross-sectional design. The study was conducted at the Faculty of Medicine, Dentistry and Health Sciences, Universitas Prima Indonesia for 2 (months) starting from February 2022–March 2022. A total of 76 subjects were involved, and each group consisted of 38 subjects. Determination of research subjects was carried out by purposive sampling technique with inclusion criteria in the form of the first-year and third-year preclinical students. In collecting data, the researcher used The Kessler Psychological Distress-10 (K-10) questionnaire. The collected data was then analyzed using an unpaired t-test. Furthermore, the results of the analysis are presented in tabular form along with interpretations. From the results of the study, it can be seen that many first-year and third-year students experience stress, and there is no significant difference between the two groups. Furthermore, the results of the study showed that there was no significant difference in the K-10 scores for first-year and third-year students based on place of residence, ethnicity, and area of ​​origin. The phenomenon of stress in medical students needs attention from the university. Preventing an academic environment by designing a curriculum that promotes collaboration rather than competition as well as providing counseling services is recommended as a preventive measure.